A variação entre futuro do pretérito e pretérito imperfeito do indicativo em orações condicionais iniciadas por "se" na fala uberlandense - Maciel-Barbosa, Tatiane Alves (2005)
This dissertation deals with the variation between the conditional and the pastimperfect indicative in conditional sentences beginning with the conjunction "if". The usage of these verb tenses alternate with simple verb constructions and verbal locutions. The author aimed to detect whether the verb forms actually alternate and the factors that determine which verb forms should be used. For the purpose of this work,linguistic factors have been analysed: size of constructions, order of sentences and formal parallelism. Besides, extra-linguistic factors such as social class and age group have also been investigated. The researcher worked with a corpus that represented the language spoken in Uberlândia, Brazil. This corpus was composed by 45 interviews with adult speakers from the city mentioned previously. The perspective of Labovian Sociolinguistics (Theory of Variation) and Parametric Sociolinguistics conducted the methodology of the research. This study shows that the past imperfect indicative is mostly used among low class and the formal parallelism favours one of the verb forms analyseds.